Media Digital dan Aplikasi Pembelajaran Bahasa Jepang yang Dimanfaatkan oleh Mahasiswa Universitas Udayana - Oeinada, I Gede (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2024)
This paper aims to explain the digital media/applications/programs (software) utilized by Japanese Literature Study Program students at the Faculty of Humanities, Udayana University, both in lectures and independent learning. Students in today's modern era are millennials who are often said to be more fluent in technology and the world of informatics than their lecturers. Therefore, lecturers can undoubtedly learn about the existence of digital media and applications that are useful for improving the quality of Japanese language learning in the future. The data in this paper was obtained through the questionnaire method by distributing questionnaires to students of the class of 2019 and 2020 using the google form facility. Furthermore, the data are analyzed descriptively and qualitatively. There were 13 questions related to the use of digital media/applications/programs and student expectations of lecturers. The findings show that 28 students in their independent learning use around 24 digital media and applications, and about six digital media and applications are used in lectures. Although 72.4% of students have already studied Japanese before attending Udayana University, the use of digital media and applications for learning Japanese is only done at the college level. In addition, it is also known that students for their lecturers hope that lecturers can better follow technological developments and learn more deeply about digital platforms that support learning so that learning will be more varied and up to date. A conclusion that can be drawn from this paper is the independence and enthusiasm for learning from students to improve their Japanese language skills beyond what has been given on campus. They feel that using digital media and applications is useful for improving their language skills, reading, listening, and writing skills.